Economic Uncertainty, Access to Finance and Digital Business Capability as Predictors of Sustainable SME Growth: The Mediating Role of Entrepreneurial Resilience in Pakistan - Najam Ul Hassan; Rehmat Ullah; Sonia Rehmat (Contemporary Issues in Social Sciences and Management Practices, 2026)
This study examines how economic uncertainty, access to finance, and digital business capability influence sustainable SME growth in Pakistan through entrepreneurial resilience. A quantitative, positivist, deductive, and cross-sectional design was adopted using 450 responses from SME owners and managers in manufacturing, retail, and services across Lahore, Karachi, Islamabad, Faisalabad, and Peshawar. PLS-SEM was applied in SmartPLS. In the model, economic uncertainty negatively predicted entrepreneurial resilience (β = −0.284, p < 0.001) and sustainable SME growth (β = −0.137, p = 0.006), whereas access to finance and digital business capability positively affected both outcomes. Entrepreneurial resilience positively predicted sustainable growth (β = 0.428, p < 0.001) and partially mediated all three predictor relationships. The model explained 54.2% of resilience and 66.8% of sustainable growth. The study integrates resource-based and dynamic-capabilities perspectives to explain how financial and digital resources produce durable growth when entrepreneurs can absorb shocks and renew strategic choices